Exploration of the South Seas in the eighteenth century : rediscovered accounts.: rediscovered accounts. Samuel Wallis's voyage round the world in the Dolphin 1766-1768 / Volume 1, (2016) - Wallis, Samuel, 1728-1795
No abstract available